Influence of Cardiopulmonary Resuscitation Coaching on Interruptions in Chest Compressions During Simulated Pediatric Cardiac Arrest*. Issue 4 (19th November 2020) - Kessler, David O.; Grabinski, Zoe; Shepard, Lindsay N.; Jones, Sara I.; Lin, Yiqun; Duff, Jonathan; Tofil, Nancy M.; Cheng, Adam
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To determine the impact of a cardiopulmonary resuscitation coach on the frequency and duration of pauses during simulated pediatric cardiac arrest. Design: This is a secondary analysis of video data collected from a prospective multicenter trial. Forty simulated pediatric cardiac arrest scenarios (20 noncoach and 20 coach teams), each lasting 18 minutes in duration, were reviewed by three clinical experts to document events surrounding each pause in chest compressions. Setting: Four pediatric academic medical centers from Canada and the United States. Subjects: Two-hundred healthcare providers in five-member interprofessional resuscitation teams that included either a cardiopulmonary resuscitation coach or a noncoach clinical provider. Interventions: Teams were randomized to include either a trained cardiopulmonary resuscitation coach or an additional noncoach clinical provider. Measurements and Main Results: The frequency, duration, and associated factors with each interruption in chest compressions were recorded and compared between the groups with and without a cardiopulmonary resuscitation coach, using t tests, Wilcoxon rank-sum tests, or chi-squared tests, depending on the distribution and types of outcome variables. Mixed-effect linear models were used to explore the effect of cardiopulmonary resuscitation coaching on pause durations, accounting for multiple measures of pause duration within teams. A total of 655 pauses were identified (noncoach n = 304 and coach n = 351). Cardiopulmonary resuscitation-coached teams had decreased total mean pause duration (98.6 vs 120.85 s, p = 0.04), decreased intubation pause duration (median 4.0 vs 15.5 s, p = 0.002), and similar mean frequency of pauses (17.6 vs 15.2, p = 0.33) when compared with noncoach teams. Teams with cardiopulmonary resuscitation coaches are more likely to verbalize the need for pause (86.5% vs 73.7%, p < 0.001) and coordinate change of the compressors, rhythm check, and pulse check (31.7% vs 23.2%, p = 0.05). Teams with cardiopulmonary resuscitation coach have a shorter pause duration than non-coach teams, adjusting for number and types of tasks performed during the pause. Conclusions: When compared with teams without a cardiopulmonary resuscitation coach, the inclusion of a trained cardiopulmonary resuscitation coach leads to improved verbalization before pauses, decreased pause duration, shorter pauses during intubation, and better coordination of key tasks during chest compression pauses.